Association between long noncoding RNA taurine‐upregulated gene 1 and microRNA‐377 in vitiligo - Alhelf, Maha; Rashed, Laila A.; Ragab, Noura; Elmasry, Maha F. (International journal of dermatology, 2022)
Background Taurine‐upregulated gene 1 (TUG1) is one of the long noncoding RNAs (lncRNAs) that plays a role in melanogenesis. MicroRNA‐377 (miRNA‐377) is a conserved noncoding RNA that regulates angiogenesis and promotes oxidative stress. Peroxisome proliferator‐activated receptors (PPARs) are components of the nuclear hormone receptor superfamily. PPAR‐γ activators stimulate melanogenesis. Interleukin (IL)‐17 has been implicated in the pathogenesis of several immunological diseases. This work aimed at detecting the expression levels of lncRNA TUG1, miRNA‐377, PPAR‐γ, and IL‐17 among vitiligo subjects and to investigate their possible role in the pathogenesis of vitiligo. Methods This study was conducted on 30 healthy controls and 30 vitiligo patients. LncRNA TUG1 and miRNA‐377 were detected in serum by real‐time polymerase chain reaction (PCR). Also, expressions of PPAR‐γ and IL‐17 were assessed in tissue by real‐time PCR. Results LncRNA TUG1 and PPAR‐γ levels were significantly downregulated in the vitiligo group compared with the control group. On the other hand, miRNA‐377 and IL‐17 were significantly upregulated in the vitiligo group compared with the control group. Conclusion This study demonstrated the dysregulated expressions of lncRNA TUG1 and miRNA‐377 in patients with vitiligo suggesting that both contributed to the pathogenesis of vitiligo that might be through PPAR‐γ downregulation and IL‐17 upregulation.